Implementasi Pendidikan Agama Islam dalam Membangun Nilai-Nilai Religius Pada Peserta Didik Upt Smp Negeri 32 Gresik - Nur Kholifah; Ahmad Thoyib Mas’udi (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2023)
Religion is a source of religious values ​​and has a very close connection to enter a person's soul. To form people who are religious and have religious values ​​within themselves, targeted education is needed. In this way, teachers in general and Islamic religious education teachers in particular strive to create a religious culture and increase religious potential in order to shape students' personalities into people who are faithful, devout and have morals. The question and aim of this research is to determine the process of implementing Islamic religious education in building religious values ​​in the UPT SMP Negeri 32 Gresik school environment and intracurricular learning. This research is field research using a qualitative descriptive approach. The data sources used were selected purposively and were snowball sampling. Data collection was carried out using observation, interviews and documentation techniques. Meanwhile, data analysis was carried out using descriptive analysis. The results of this research show that: The implementation of Islamic religious education in building religious values ​​in the UPT SMP Negeri 32 Gresik environment was carried out well and effectively. Then related to programs in a special curriculum regarding religion, also memorizing selected letters in the Koran, then the example and discipline provided by all school members. Intracurricular learning of Islamic religious education in building religious values ​​of students at UPT SMP Negeri 32 Gresik